1994
DOI: 10.1152/jappl.1994.77.1.463
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of capillary pathway size and neutrophil deformability to neutrophil transit through rabbit lungs

Abstract: Neutrophil margination within the pulmonary capillary is due to a delay in their transit compared with that of red blood cells (RBC). This delay has been attributed to the large fraction of capillary segments that are narrower than spherical neutrophils and differences between the time required for deformation of neutrophils and that required for deformation of RBC. This study investigated the characteristics of neutrophil deformation in vivo and the perfusion patterns of segments within capillary pathways. St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
71
1

Year Published

1997
1997
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(76 citation statements)
references
References 0 publications
4
71
1
Order By: Relevance
“…In addition to vascular adhesion molecule interaction with stem cells, cell type-specifi c deformability might also be involved in pulmonary stem cell passage. Although our data do not allow us to further speculate on this issue, Wiggs et al demonstrated the impact of capillary pathway size and neutrophil deformability on neutrophil transit through rabbit lungs [16]. Therefore, the groups demonstrating the majority of infused stem cells to be trapped inside the pulmonary system.…”
Section: Resultsmentioning
confidence: 61%
“…In addition to vascular adhesion molecule interaction with stem cells, cell type-specifi c deformability might also be involved in pulmonary stem cell passage. Although our data do not allow us to further speculate on this issue, Wiggs et al demonstrated the impact of capillary pathway size and neutrophil deformability on neutrophil transit through rabbit lungs [16]. Therefore, the groups demonstrating the majority of infused stem cells to be trapped inside the pulmonary system.…”
Section: Resultsmentioning
confidence: 61%
“…At branch points, this celldepleted wall region allows a progressively smaller fraction of cells to enter the daughter vessel than the parent vessel, causing a progressive reduction in hematocrit as blood courses its way from arterioles to capillaries (55). However, in contrast to RBCs, the neutrophil concentrations in capillaries are up to 40 -80 times higher than in larger blood vessels (56,57). Although some differences can be explained by the longer neutrophil transit times through capillaries, chemokine gradients may promote neutrophil circulation via narrow capillaries instead of the larger "thoroughfare" arteriolovenular shunts (58).…”
Section: Discussionmentioning
confidence: 99%
“…Studies in humans undergoing cardiac catheterization show that alveolar compression results in an immediate arteriovenous difference of PMN across the lung that reverses when alveolar pressure is returned to normal (21). Mechanical deformation of PMN has been demonstrated in pulmonary microvessels (5), and Wiggs et al (29) have shown that PMN of ,7 µm in diameter negotiate the capillary bed in the same way as 4-µm nondeformable beads. These findings indicate that the PMN deform in the pulmonary capillary bed, but whether this deformation is an active or passive process remains to be determined.…”
mentioning
confidence: 99%